2021
DOI: 10.1111/1911-3846.12725
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Timing and Management's Remediation Actions in Preventing Failed Remediation of Material Weaknesses in Internal Controls*

Abstract: Prior research finds that signals of remediation of internal control weaknesses do not guarantee that all weaknesses are fully resolved. However, why certain remediation strategies fail is unclear. This study examines how remediation timing and actions affect the likelihood of a failed remediation. I predict and find that the likelihood of a failed remediation is decreasing in both the time a company takes to remediate and in the extent of remediation actions employed. Importantly, this study documents that di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 59 publications
0
1
0
Order By: Relevance
“…These measures are more likely to win market trust and tolerance [ 38 ], which can, in turn, help firms access resources and bolster their motivation to practise ESG. These findings are compatible with prior theories that firms' operating performance improves in the year following the remediation of material deficiencies [ 26 , 27 , 40 ]. As previously mentioned, remediation actions are important signals that a firm's management is taking steps toward improving, which garners more trust and support for the firm to invest in ESG, ultimately promoting ESG performance.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…These measures are more likely to win market trust and tolerance [ 38 ], which can, in turn, help firms access resources and bolster their motivation to practise ESG. These findings are compatible with prior theories that firms' operating performance improves in the year following the remediation of material deficiencies [ 26 , 27 , 40 ]. As previously mentioned, remediation actions are important signals that a firm's management is taking steps toward improving, which garners more trust and support for the firm to invest in ESG, ultimately promoting ESG performance.…”
Section: Resultssupporting
confidence: 90%
“…Firstly, ICMDR information disclosure significantly and positively influences ESG performance, the result that remains valid across various endogeneity concerns and robustness tests. The results suggest that firms that engage in ICMDR information disclosure have better ESG performance, which is consistent with the relevant theoretical frameworks and with signalling and stakeholder theory, as well as with the findings reported in previous literature [ 26 , 27 , 40 ]. Secondly, our analytical results obtained using the mediating effect model show that ICMDR disclosure positively affects ESG performance through the mitigation of financial risk.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Francis et al (2017) further stressed that traditional, low-turnover boards might lack the necessary comprehension of the unique dynamics of alternative finance models. Imdieke (2022) postulated, this lack of expertise might increase the risk perception of lenders, subsequently increasing the cost of debt. Ferreira et al (2018) concluded by stating that these boards might not cater effectively to the expectations of alternative finance providers, further elevating debt costs.…”
Section: Hypothesis Developmentmentioning
confidence: 99%